Effectiveness of Implementing Digital Fundraising and Fund Accounting at BAZNAS North Sumatra - Hanifah Restu Putri; Yenni Samri Juliati Nasution; Rahmi Syahriza (Universitas Nurul Jadid, 2024)
The number of poor people in Indonesia in 2023 will reach 25.90 million people, this is a quite serious problem for the country. Zakat is a means of mutual cooperation that can help this imbalance. Internet penetration in North Sumatra is the highest on the island of Sumatra based on the APJII survey in early 2024, this is the spearhead of all types of digitalization applications. This fact makes us aware that the potential for zakat should increase further and make it easier for BAZNAS North Sumatra Province to collect funds. This research aims to measure the effectiveness of implementing digitalization in compiling and reporting accounting. The data collection method uses researchqualitatively based with a phenomenological approach.Based on the research results, the implementation of digital fundraising can be said to be effective, but it is not yet effective in targeting accuracy, one of which is due to a lack of social engagement on social media. For fund accounting, which is a reporting rule for non-profit organizations, BAZNAS North Sumatra Province has implemented regulations with PSAK 109 and reporting has been digitized and automated.